145 Incorporating Intraoperative Mechanomyography to Peripheral Nerve Decompression Surgery. (April 2023) - Taghlabi, Khaled; Guerrero, Jaime; Cruz-Garza, Jesus; Javeed, Saad; Dibble, Christopher; Ray, Wilson Zachary; Faraji, Amir H.
Abstract : INTRODUCTION: Considerable progress has been made in the development of novel intraoperative nerve monitoring technologies. Recent studies demonstrated the high sensitivity of mechanomyography (MMG) in detecting nerve function as compared to traditional electromyographic recording. MMG reflects the mechanical vibrations of single motor units detected via accelerometer sensors and is therefore indicative of underlying axonal integrity. METHODS: A total of 20 consecutive patients undergoing decompression procedures for ulnar nerve (8 patients) or common peroneal nerve (12 patients) neuropathies were included. Four patients did not have MMG signals elicited: 1 ulnar and 3 common peroneal nerve patients. Intraoperatively, the nerves were stimulated via MMG ball tip electrode probe starting at 0.1 mA threshold and increasing by 0.1 mA increments until target muscle activity was noted. The lowest threshold current required to elicit a muscle response was recorded prior to decompression and following proximal and distal decompression. RESULTS: Of the patients, 80% (16/20) had MMG signals detected and recorded. The mean pre-decompression stimulus threshold was 1.59 ± 0.77 mA. Following surgical decompression, a statistically significant improvement in mean MMG stimulus threshold was noted (0.47 mA ± 0.13, p < 0.0001). The average stimulus threshold change for the common peroneal nerve patients was -0.80 mA (p = 0.001), and -1.48 mA (p = 0.002) for ulnar nerve patients. Post-operatively, all patients endorsed symptomatic improvement with no complications. CONCLUSIONS: MMG is an established technique that may provide objective intraoperative guidance in determining the extent of surgical nerve decompression. Lower stimulus thresholds likely represent increased sparing of axonal tissue, which may correlate with improved functional recovery. Future work should focus on validating normative values of MMG stimulus thresholds in various nerves and establishing clinical associations with functional outcomes.